Analisis Bauran Promosi Pariwisata Budaya Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toraja Utara (Jurnal Destinasi Pariwisata, 2025)
The North Toraja Regency's Tourism Office plays a vital role in showcasing the region's unique appeal. A recent study delved into their strategies, examining both the existing tourism potential and the promotional methods employed. The research encompassed the office's efforts in promoting natural beauty, rich cultural heritage, and their use of various promotional tools like advertising, sales promotion, direct marketing, public relations, and personal selling. Utilizing qualitative data from observations, interviews, documentation, and literature, the study found that the Tourism Office's approach aligns well with a comprehensive promotional mix. Their advertising spans print media and the internet, while sales promotions include engaging video demonstrations. Direct marketing is executed through email and a dedicated website, and public relations efforts involve both digital communication and tourism training initiatives. Notably, personal selling is actively pursued through direct sales engagements in various countries, demonstrating a proactive global outreach. Despite these efforts, the study identified barriers hindering tourism development in North Toraja. To overcome these, it's crucial to enhance human resource capacity through more intensive training programs. Furthermore, diversifying funding sources and optimizing budget management are essential steps. Strengthening the application of information technology in promotions and maximizing the use of digital media are also key to unlocking North Toraja's full tourism potential.